Spectrophotometric Studies of Charge Transfer Complex between p-Chloranil and Certain Aromatic Amines at 302 K - Pratibha, B. (Asian Journal of Chemistry, 2012)
Spectrophotometric studies of charge transfer complexation between p-chloranil and aromatic amines like N,N-dimethyl amine, N-methyl amine, o-toludine, benzyl amine and diphenyl amine have been carried out in chloroform medium. All the complexes show charge transfer band in the visible region and they form 1 : 1 complexes of n-p type. The relevantspectral parameters for the change transfer complex like association constant Gibb’s free energy, molar extinction coefficient, ionization potential and resonance energy were calculated. A comparative study on the evaluation of association constant is investigated by modified B-H Scott and F-H-W equations, besides proposing a semiempirical McConnel equation.